Pendampingan Implementasi Digital Marketing Sebagai Strategi Pemasaran UMKM Sentra Tape di Desa Tegalwaru Kabupaten Jember - Yosefa Sayekti; Indah Purnamawati; Ririn Irmadariyani; Bambang Irawan; Aisa Tri Agustini (Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2023)
Partner of this Community Service Activity are are Micro, Small and Medium Enterprises (MSMEs) engaged in Snack/food manufacturing, namely tape (fermented cassava) located in Tegalwaru Village, Mayang District, Jember Regency. There are 10 MSMEs partners whose businesses have been established for a long time. However, the marketing activities are still traditional. For this reason, these MSMEs need to be given development related to their marketing and given training on the importance of digital marketing as a marketing strategy for MSMEs so that the marketing system is even better so that it can expand the scope of its target market and can increase sales. One of the digital media used to market products is Instagram. In addition, MSMEs are also given assistance in updating their product packaging to make it look more attractive so that it can attract consumer interest. The outputs resulting from this service activity are re-branding packaging, as well as maximizing the use of Instagram social media. The method used is to provide materials and training in the form of Focus Group Discussions (FGD). From the results obtained in this activity, it is suggested that the use of digital marketing should be more optimized so that it can produce the desired target, namely increasing market share and sales of MSMEs.